2009
DOI: 10.1021/ie900230s
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Flow Regimes in Vertical Pneumatic Conveying

Abstract: Pneumatic conveying is an important technology in industries to transport bulk materials from one location to another. Different flow regimes have been observed in such a transportation process depending on operational conditions, but the underlying fundamentals are not clear. This paper presents a three-dimensional numerical study of vertical pneumatic conveying by a combined approach of discrete element model for particles and computational fluid dynamics for gas. The approach is verified by comparing the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 63 publications
(122 reference statements)
0
40
0
Order By: Relevance
“…[44][45][46][47] On the contrary, CFD-DEM has no such limitations and is, thus, applicable to a wide range of flow conditions. 30,48 With this realization, CFD-DEM has been increasingly used to study pneumatic conveying in various aspects, including flow regimes, as recently summarized by Kuang et al 49 These studies can improve the understanding of pneumatic conveying. However, to date, most of these studies were based on simplified models where 3-D particle flow was sometimes treated as 2-D, and gas flow was 2-D or 1-D.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] On the contrary, CFD-DEM has no such limitations and is, thus, applicable to a wide range of flow conditions. 30,48 With this realization, CFD-DEM has been increasingly used to study pneumatic conveying in various aspects, including flow regimes, as recently summarized by Kuang et al 49 These studies can improve the understanding of pneumatic conveying. However, to date, most of these studies were based on simplified models where 3-D particle flow was sometimes treated as 2-D, and gas flow was 2-D or 1-D.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been applied to the study of flow regimes in vertical pneumatic conveying. 49 However, to date, comprehensive 3-D CFD-DEM modeling and analysis of the flow regimes in horizontal pneumatic conveying have not been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the model based on the CFD-DEM approach is the first attempt to propose the use of the CFD-DEM method for the investigation of barite sag behaviour, keeping in mind that the system is a liquid-solid flow. Past researchers [15][16][17][18] have employed this approach in the study and analysis of other systems, but only considering gas-solid flows. The only exception is Zhao and Shan [19] and Akhshik et al [20] who performed simulation of the behaviour of fluid-particle interactions for applications relevant to mining and geotechnical engineering [19] and the investigation of the effect of drill pipe rotation on cuttings transport behaviour [20].…”
Section: Limitations and Further Developmentmentioning
confidence: 99%
“…The tangential damping force, F , , is expressed as Accordingly, the tangential torques acting on th barite particle due to barite particle collision ( th barite particle) is expressed as [15] T , = r × (F , + F , ) , (A.11) and the torque to resist rolling action on th barite particle due to barite particle collision ( th barite particle) is given as [15] T , = − r F , , 12) where r is a vector from the center of mass of barite particle to the contact point, is the rolling friction coefficient, and is the relative angular velocity of barite particle to particle , ( − ). The torques T , and T , are generated by the tangential contact forces and the rolling friction, respectively.…”
Section: Appendixmentioning
confidence: 99%
“…It was showed that the solid phase turbulence plays a significant role in numerical predictions of pneumatic conveying of 1.91 mm particles and the capability of those models depends on tuning of the parameters of slip-wall boundary condition. The combined "Computational Fluid Dynamics -Discrete Element Method (CFD-DEM)" developed by Kuang et al (2009) gives satisfactory predictions for vertical pneumatic conveying characteristics. The mechanisms underlying the relation between pressure drop and gas velocity were analysed for dilute and dense phases.…”
Section: Introductionmentioning
confidence: 99%